Peningkatan Kesejahteraan Wanita Pesisir Dengan Pengolahan Udang Menjadi Nugget di Desa Pahlawan Kecamatan Tanjung Tiram Kabupaten Batu Bara - Wahyu Indah Sari; Rusiadi (MARHALADO : Jurnal Pengabdian kepada Masyarakat, 2023)
The abstract contains a brief description of the purpose of community service, the methods used, and the results of community service. The emphasis of abstract writing is mainly on the results of community service. Abstracts are written in Indonesian and English. Abstract typing is done single-spaced with margins that are narrower than the right and left margins of the main text (max. 200 wordThis service is carried out to form an understanding and utilization of fishermen's catches regarding the productivity of coastal women who can help meet the needs of daily life by not only expecting sales results from the catch of fishermen (their husbands/families) but are expected to be able to provide development and insight into coastal women that fishermen's catches can be used as product development that can increase their family's income. Then it is also hoped that these coastal women will be able to market their products according to their economic market targets so that the needs of fishing families can be fulfilled and the welfare of fishing families can be achieved. The plan for this service activity will be carried out for 1 day with the socialization of the productivity of coastal women, 1 day of product manufacturing training, making brands, packaging, and product distribution and 1 day of evaluation of the results by re-observing the economic development of coastal women in Pahlawan Village, Tanjung Tiram District, Batu Bara Regency.